2022
DOI: 10.1039/d1sc04503b
|View full text |Cite
|
Sign up to set email alerts
|

Facile conversion of ammonia to a nitride in a rhenium system that cleaves dinitrogen

Abstract: Rhenium–PNP complexes split N2 to nitrides, but the nitrides do not give ammonia. Here, the thermodynamics of the hypothetical N–H bond forming steps are evaluated through the reverse reaction, showing that the first H addition is the bottleneck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…However, the comparison between experimental 119 Activation of ammonia and hydrazine is a very active eld of research. [59][60][61][62][63][64] Besides coordination induced bond weakening (Scheme 5e), [59][60][61] oxidative addition at transition metal complexes [65][66][67][68][69] or main group element compounds 56,57,[70][71][72][73][74][75][76][77][78][79][80] (Scheme 5a and b), cooperative reactions with metal-ligand systems [81][82][83][84][85] and a N-heterocyclic germylene 55 were reported (Scheme 5c and d). These literature examples of cooperative metal-ligand reactivity exhibit formation of a M-NH 2 moiety (M = Ru, Rh, Ir, Ni; Ge) and transfer of a hydrogen atom to the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…However, the comparison between experimental 119 Activation of ammonia and hydrazine is a very active eld of research. [59][60][61][62][63][64] Besides coordination induced bond weakening (Scheme 5e), [59][60][61] oxidative addition at transition metal complexes [65][66][67][68][69] or main group element compounds 56,57,[70][71][72][73][74][75][76][77][78][79][80] (Scheme 5a and b), cooperative reactions with metal-ligand systems [81][82][83][84][85] and a N-heterocyclic germylene 55 were reported (Scheme 5c and d). These literature examples of cooperative metal-ligand reactivity exhibit formation of a M-NH 2 moiety (M = Ru, Rh, Ir, Ni; Ge) and transfer of a hydrogen atom to the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…We propose that nitride ligand insertion into the B−H bond of 9-BBN may proceed by one of two pathways: (1) a concerted reaction involving direct nitride insertion into the B−H bond or (2) a stepwise pathway in which formation of a nitride−borane adduct is followed by [1,2]-migration of the hydrogen atom (Scheme 7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, it has recently been shown that there is little driving force for N−H bond formation in N 2 -derived rhenium nitride complexes, where the N−H bond dissociation free energy (BDFE) is less than 50 kcal/mol. 2 Even nitrides that are not generated from N 2 appear to form relatively weak N−H bonds, as demonstrated by an iron(IV) nitride, which only reacts with TEMPO-H (BDFE = 65.0 ± 1.3 kcal/mol) to generate ammonia. 3,4 Given these considerations, we envisioned an alternative strategy for nitride functionalization involving nitride insertion into an H−E bond.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic evaluation of the thermodynamics of the key N–H bond cleavage reactions required in catalysis can provide critical information to facilitate the design of new catalyst systems. The first N–H bond dissociation free energy (BDFE) of NH 3 is 100.3 kcal/mol in the gas phase but is substantially decreased by coordination to a transition metal. , Although the first BDFE of ammonia is high, inclusion of the subsequent formation of the N≡N bond in the evaluation of the thermodynamics gives an effective, average BDFE of 53.2 kcal/mol in MeCN …”
Section: Introductionmentioning
confidence: 99%